2004
DOI: 10.4269/ajtmh.2004.71.55
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition as an Underlying Cause of Malaria Morbidity and Mortality in Children Less Than Five Years Old

Abstract: Undernutrition is highly prevalent in many areas in which morbidity and mortality from malaria is unacceptably high. That undernutrition exacerbates diarrhea and respiratory infections is widely demonstrated; however, research suggests that it may exacerbate, palliate, or have little effect on malaria outcomes. This review examines the global burden of malaria associated with various nutrient deficiencies as well as underweight status in children 0-4 years of age. Although the association is complex and requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
178
3
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(205 citation statements)
references
References 90 publications
12
178
3
6
Order By: Relevance
“…There is experimental evidence that vitamin A supplementation in children is associated with a reduction from 23 to 30% in mortality risk and attenuation in disease severity (59) There is also a general consensus that PEM is associated with greater malaria morbidity and mortality in humans (65). Supporting this observation, controlled clinical trials of either vitamin A or zinc supplementation indicated that these nutrients can substantially reduce clinical malaria outbreaks (66,67). Opinions regarding the effect of certain micronutrients, as iron, for example, are still contradictory (68,56).…”
Section: Malnutrition Increases Risk Of Infectionmentioning
confidence: 79%
“…There is experimental evidence that vitamin A supplementation in children is associated with a reduction from 23 to 30% in mortality risk and attenuation in disease severity (59) There is also a general consensus that PEM is associated with greater malaria morbidity and mortality in humans (65). Supporting this observation, controlled clinical trials of either vitamin A or zinc supplementation indicated that these nutrients can substantially reduce clinical malaria outbreaks (66,67). Opinions regarding the effect of certain micronutrients, as iron, for example, are still contradictory (68,56).…”
Section: Malnutrition Increases Risk Of Infectionmentioning
confidence: 79%
“…Fe deficiency is known to decrease immune function, but some investigators have also hypothesized that Fe supplementation increases infectious disease (17) . Indeed, some controversy exists concerning Fe-deficiency anaemia in that it does not appear to contribute to growth faltering (18) .…”
mentioning
confidence: 99%
“…A possible explanation is because skin infections do not alter dietary intake as much as respiratory infections or gastroenteritis. Other studies have demonstrated a relationship between malaria and nutrtion, 21,22 but the low number of children in this study that is diagnosed with malaria, with a total of 5 makes it hard to show a significant effect. From the result of this study, regarding nutritional status in children, the focus should not be solely on improving the anthropometry status of children, but to also consider the overall health condition, because upper respiratory tract infections and gastroenteritis is caused by many different factors.…”
Section: Relationship Between Weight Gain and Infectionmentioning
confidence: 47%